2019
DOI: 10.1108/jsm-01-2018-0045
|View full text |Cite
|
Sign up to set email alerts
|

Trust in humanoid robots: implications for services marketing

Abstract: Purpose Service robots can offer benefits to consumers (e.g. convenience, flexibility, availability, efficiency) and service providers (e.g. cost savings), but a lack of trust hinders consumer adoption. To enhance trust, firms add human-like features to robots; yet, anthropomorphism theory is ambiguous about their appropriate implementation. This study therefore aims to investigate what is more effective for fostering trust: appearance features that are more human-like or social functioning features that are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
212
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(228 citation statements)
references
References 99 publications
(179 reference statements)
13
212
1
2
Order By: Relevance
“…Second, the study contributes to trust literature concerning interactions with AI‐based technology (Foehr & Germelmann, 2020; van Pinxteren et al, 2019). Specifically, results highlight the need of understanding peculiarities of the trust development process with and toward VAs, while demonstrating the prominent role of social elements; namely, social presence and social cognition, as unique antecedents for developing users' trust toward VAs (van Doorn et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
“…Second, the study contributes to trust literature concerning interactions with AI‐based technology (Foehr & Germelmann, 2020; van Pinxteren et al, 2019). Specifically, results highlight the need of understanding peculiarities of the trust development process with and toward VAs, while demonstrating the prominent role of social elements; namely, social presence and social cognition, as unique antecedents for developing users' trust toward VAs (van Doorn et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
“…As indicated above, previous literature on robotics has mostly focused on aesthetics and physical appearances, often with an assumption of a positive correlation between robot human-likeness and users' acceptance (Walters et al, 2008). However, the optimal level of human-likeness (Tinwell, Grimshaw, & Williams, 2011b) has not been established clearly (Burleigh, Schoenherr, & Lacroix, 2013;Rosenthal-von der Püthen & Kramer, 2014), suggesting the moderating effects of customer features or encounter characteristics, as we address subsequently (Van Pinxteren et al, 2019). In a general sense, higher levels of human appearance seem to amplify emotional attachment, induce positive perceptions and attitudes, and increase trust in and preference for robots (Tussyadiah & Park, 2018;Van Pinxteren et al, 2019).…”
Section: Aestheticsmentioning
confidence: 84%
“…However, the optimal level of human-likeness (Tinwell, Grimshaw, & Williams, 2011b) has not been established clearly (Burleigh, Schoenherr, & Lacroix, 2013;Rosenthal-von der Püthen & Kramer, 2014), suggesting the moderating effects of customer features or encounter characteristics, as we address subsequently (Van Pinxteren et al, 2019). In a general sense, higher levels of human appearance seem to amplify emotional attachment, induce positive perceptions and attitudes, and increase trust in and preference for robots (Tussyadiah & Park, 2018;Van Pinxteren et al, 2019). This positive effect likely arises because a human appearance of a technological object increases customers' access to a human schema, due to the human-like congruency (e.g.…”
Section: Aestheticsmentioning
confidence: 90%
See 1 more Smart Citation
“…In general, robot appearance (from anthropomorphic to functional) influenced users' likeability and empathy: less human looking robots were less liked and users' empathy was stronger toward anthropomorphic robots [22,23]. Further studies revealed that anthropomorphic design features (e.g., facial expression, gestures, communication) increased humans' trust and intention to use robots [24,25].…”
Section: Introductionmentioning
confidence: 95%